Using a Virtual Plant to Support the Development of Intelligent Gateway for Sensors/Actuators Security. Issue 1 (July 2017) - Toublanc, Thomas; Guillet, Sébastien; de Lamotte, Florent; Berruet, Pascal; Lapotre, Vianney
Abstract: Our industries are facing a new revolution, about Connectivity, Information and Network. Nowadays, the threats on industrial cyber physical systems are not just theoretical. They can do major damage to our real world through cyberspace. In this paper, a demonstrator for security on Sensor/Actuator network in industrial applications is proposed. It consists of an operational part simulator SimSED and automation emulator Straton Runtime, linked together by TCP/IP. This demonstrator is dedicated to evaluate a secure gateway for security in Network Control System (NCS). Two support bricks of the gateway are introduced. The first one is a filter for demonstrator protocol. The second one an auto-generated input/output model which represents the protected system. The intelligent gateway will support safety, reliability and resilience objectives for security of NCS.